Effect of eryngo (Eryngium caucasicum Trautv) on primary dysmenorrhea: A randomized, double-blind, placebo-controlled study - Elham Behmanesh; Mouloud Agajani Delavar; Mohammad Kamalinejad; Soraya Khafri; Hoda Shirafkan; Seyyed Ali Mozaffarpur (Elsevier, 2019)
Objective: This study strove to investigate the safety and effectiveness of Eryngo in the treatment of primary dysmenorrhea. Materials and methods: The researchers conducted a blinded, randomized, trial design on 169 women, 15-30 years of age, who had been diagnosed with primary dysmenorrhea at Babol University of Medical Sciences. Subjects were randomly assigned to receive 5 ml syrup of Eryngo, placebo, or Ibuprofen (200 mg) three times a day (15 ml/day), from one day prior to the onset of bleeding for five days. The degree of dysmenorrhea was reported by two measures; Visual analogue scale (VAS), as a primary outcome, and the assessment of dysmenorrhea severity (VMS), as a secondary outcome at 4 menstrual cycles: at pretreatment phase, at the first menstrual cycle, at the second menstrual cycle, and the third menstrual cycle without drug. Results: The reduced peak-pain differed by the treatment length in women treated for two menstrual cycles: 4.2 (1.0) cm in the Eryngo group, 4.3 (0.0) cm in the Ibuprofen group, and 0.9 (0.1) cm in the placebo group (P < 0.0001). No serious side effects were reported in all groups under study. According to the results, minor side effects did not increase in the Eryngo group when compared with the placebo group. Conclusion: Eryngo relieved dysmenorrhea as effectively as Ibuprofen did. Thus, Eryngo could be regarded as a new herbal remedy for the treatment of dysmenorrhea. However, in order to prescribe Eryngo as herbal remedy, rigorous research studies are required to establish its efficacy by investigating its chemical, pharmacologic, and therapeutic properties. Keywords: Dysmenorrhea, Herbal medicine, Women